Índice HOMA-IR como predictor de reducción de exceso de peso en pacientes con índice de masa corporal (IMC)≥35kg/m2 sometidos a gastrectomía vertical - Casas-Tapia, Cristina (2020)
Introduction: Bariatric surgery is considered the most effective treatment for severe obesity. However, it is not clear if patients with diabetes mellitus or insulin resistance have the same response than patients without those conditions. Our objective was to evaluate association between pre-surgical HOMA-IR index and percentage of excess weight loss (EWL%) one year after bariatric surgery using sleeve gastrectomy. Methods: Retrospective cohort including patients ≥ 18 years old with BMI ≥ 35 kg/m2, who underwent primary sleeve gastrectomy between 2014-2017 at the Avendaño Medical Center, Peru. Only patients with Type 2 Diabetes, Hypertension, or Dyslipidemia were included. EWL% ≥ 60% one year after surgery was considered satisfactory. Crude and adjusted Lineal and Poisson regression with robustness was used to assess statistical associations with EWL%. Results: Ninety-one patients were included with a median of 34 years, and 57.1% were women. 85.7% had insulin resistance as per HOMA-IR. One year after surgery, 76.9% had a satisfactory EWL%. The lineal model showed. 29% less EWL% per each extra year of life (P = .019), and. 93% more EWL% per each extra HOMA-IR point (P = .004). The adjusted Poisson model showed 2% lower risk of having a satisfactory EWL% per each additional year of life (P = .050), and 2% more chance of success per each additional HOMA-IR point (P = .038). Conclusions: There was association between a higher pre-surgical HOMA-IR index and increased EWL% one year after surgery. It is possible that insulin resistance does not affect negatively sleeve gastrectomy outcomes.